Παρουσίαση Τμήματος Αγροτικής Οικονομίας & Αναπτύξεως - Γεωπονικό Πανεπιστήμιο Αθνών (Agricultural University of Athens (official channel), 2021)
: suggested that i should sing word by word but i said i wanted to sing Cream I'm trying to prove you're good or bad or tend to fill the ground That's not my fate, that's not your land I'm trying to prove you're good or bad or tend to fill the ground That's not my fate, that's not your land That's not my fate, that's not your land Restless thoughts and options you're so proud of when you know Or if you don't they disappear and they feel wrong And they feel wrong, and they feel wrong Right you look right again you broke your right To be the same like them I want them real I want them live their life in peace Lost they seem to hesitate my thoughts are black Your wants are reprimand I want you cool I want you live your life in colors Carve your name on fences, walls or seats The road you walk was just a street There are no miles or hidden roads Rising up the kids can be destroying Can be exhausting but a smile comes when they grow Restless thoughts and options you're so proud of when you know Or if you don't they disappear and they feel wrong Right you look right again you broke your right To be the same like them I want them real I want them live their life in peace Lost they seem to hesitate my thoughts are black Your wants are reprimand I want you cool I want you live your life in colors